Humanitarian Concerns and Deportation Orders Under the Immigration Act 2009: Are International Obligations Enough Protection for the Immigrant with Mental Illness? - Fadgen, Timothy P; Charlton, Guy (Victoria University of Wellington Law Review, 2012)
New Zealand has long prided itself as a champion for human rights within the international community. At the same time, local immigration laws have been tightened and long-standing recognition of the rights of migrants has been eroded. One sub-class of migrants, and the focus of this article, are migrants suffering from a mental illness. This article addresses the narrow question of rights accorded these individuals under the Immigration Act 2009 in light of New Zealand's long-standing international human rights obligations. The article questions the protection afforded an individual facing deportation under this Act in light of statutory changes that no longer require an immigration officer to issue a justification for issuing an order of deportation and argues, in light of this legislative change, that a "hard look" standard of review is required if the judiciary is to continue to have any meaningful role in ensuring executive compliance with international obligations.